Description of a new Neotropical spider genus in the family Ctenidae Keyserling, 1877 (Araneae: Lycosoidea) from the Brazilian Amazon rainforest - Pereira, Maria Paula; Labarque, Facundo; Polotow, Daniele (Zootaxa, 2020)
A new Neotropical genus of Ctenidae from the Brazilian Amazon rainforest is described based on male and female characters: Bulboctenus gen. nov. Three new species are described for the genus: Bulboctenus kayapo sp. nov., Bulboctenus itunaitata sp. nov. and Bulboctenus munduruku sp. nov. The genus can be distinguished from other Ctenidae by males with median apophysis oriented horizontally, perpendicular to the tegulum, RTA strongly excavated anteriorly, metatarsi III and IV with bulbous setae ventrally, sternum and coxae with thick setae; and females with median sector of the epigyne hexagonal with two posterior conical projections ventrally and elevated lateral margins. Discussion on the modification on the leg setae across the Neotropical Ctenids species are given.